Analisis Kesalahan Siswa Mengubah Bentuk Akar Dalam di Kelas X Fase E. 7 SMA N 1 Harau - Tri Rahma Santika; Tasnim Rahmat; Cendro Cesbajar (Pusat Riset dan Inovasi Nasional, 2023)
In solving mathematical problems, students must find errors in understanding a material given by the teacher, this can happen due to several factors. In this article it aims to analyze the errors and difficulties experienced by students of class X Phase E.7 in studying the material of root forms. One way that can be done is by identifying the cause of students' mistakes in doing math problems during the mathematics learning process in the classroom. This research uses a qualitative descriptive approach. With research instruments in the form of field observations and student learning outcomes. The research subjects of class X Phase E.7 SMA N 1 HARAU students were 7 students who had the highest final semester exam scores.